2016
DOI: 10.1111/jfb.13116
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology and feeding habits of the prickly dogfishOxynotus bruniensis

Abstract: The reproductive biology and diet of prickly dogfish Oxynotus bruniensis, a deep-sea elasmobranch, endemic to the outer continental and insular shelves of southern Australia and New Zealand, and caught as by-catch in demersal fisheries, are described from specimens caught in New Zealand waters. A total of 53 specimens were obtained from research surveys and commercial fisheries, including juveniles and adults ranging in size from 33·5 to 75·6 cm total length (L ). Estimated size-at-maturity was 54·7 cm L in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…Examinations of the feeding behaviour of Oxynotus centrina suggest that oxynotids are highly specialized preying on chondrichthyan eggs (Finucci, Bustamante, Jones, & Dunn, ; Guallart et al, ), which most likely has led to significant morphological adaptations. Herein, the fossil taxon † Oxynotus crochardi is sister to extant Oxynotus centrina (Figure ) due to distinctive dental features.…”
Section: Discussionmentioning
confidence: 99%
“…Examinations of the feeding behaviour of Oxynotus centrina suggest that oxynotids are highly specialized preying on chondrichthyan eggs (Finucci, Bustamante, Jones, & Dunn, ; Guallart et al, ), which most likely has led to significant morphological adaptations. Herein, the fossil taxon † Oxynotus crochardi is sister to extant Oxynotus centrina (Figure ) due to distinctive dental features.…”
Section: Discussionmentioning
confidence: 99%
“…Chimaera carophila have not been recorded any larger than observed in this study, but unsexed H. homonycteris have been measured up to 110 cm L C by research trawl surveys (maximum length in this study was 99·8 cm L C ). A rarity of reproductive females has been reported for other New Zealand chondrichthyans (Wetherbee, 1996;Finucci et al, 2016b) and in the North Atlantic (Holt et al, 2013;Moura et al, 2014). Chimaerids may segregate by sex and size (Quinn et al, 1980), which may be a trade-off for minimizing intraspecific competition and sexual conflict (Wearmouth & Sims, 2008) and female chimaerids have been found at greater depths than their male counterparts (Holt et al, 2013).…”
Section: B I O L O G I C a L S A M P L I N Gmentioning
confidence: 99%
“…Plunket's shark, Scymnodon plunketi (Waite, 1910), and prickly dogfish, Oxynotus bruniensis (Ogilby, 1893), were close to meeting the criteria for the threatened categories, and were thus listed as NT. Both species have life histories suggestive of low productivity (Finucci, Bustamante, Jones, & Dunn, ; Francis, Jones, Ó Maolagáin, & Lyon, ), as well as high distribution overlap with fishing across much of their range (45–60% and >60% overlap respectively) (Ford et al, , ). Although research trawl survey relative biomass showed no trends in the fisheries management areas where Plunket's shark and prickly dogfish have been caught, monitoring of the species is poor (coefficient of variation CV of biomass estimates ≥40%), and, at least in the case of Plunket's shark, reasons for lack of trends are unknown (Francis, Roberts, & MacGibbon, ).…”
Section: Resultsmentioning
confidence: 99%